SELF-EFFICACY AND BEHAVIORAL CHANGES ON EXERCISE ON HEALTH-RELATED QUALITY OF LIFE IN MIDDLE-AGED WOMEN OF KLANG VALLEY - Hassan, Hafizah Che (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The present study aims to explore the effects of self-efficacy and behavioral changes on exercise that impact on the health-related quality of life (HRQoL) of middle-aged Malaysian women. Methods: A questionnaire-based data collection was performed from October 2013 to March 2014 in the Klang Valley, Malaysia. Analysis of data was performed by SPSS (vs. 21.0) after recording body mass index, general health, physical health status, self-efficacy, and self-awareness associated with HRQoL. Correlation between the parameters was performed using Pearson's correlation coefficients, and the reliability test was conducted using Cronbach's alpha (Î±). Results are mentioned as significant when p-values are found to be <0.05. Results: Findings of the study indicate though women of Klang Valley suffer from few health problems, they prefer exercise to maintain their HRQoL. It has been observed that self-efficacy and behavioral changes for exercise related QoL are affected by several factors, such as education, monthly income, marital status, and even ethnicity. Among 736 respondents, only 304 made a change in their exercise regime, and the level of change is about 58.4% had made small increase and followed by 41.3%. Women with higher self-efficacy (50.35%) made changes by taking up exercise to have a healthy lifestyle. Conclusions: This study portrays that women of Klang Valley, Malaysia, are inflicted with quite a good self-efficacy to exercise, which impacts their HRQoL.